Assessment of obesity and body Image satisfaction amongst students of AMC MET Medical College, Ahmedabad, Gujarat / Vyas Sheetal … [et al.] - Sheetal, Vyas; Chitra, Pandya; Rishita, Mehta; Dhwani, Mehta; Mohak, Mankad; Aneri, Modh (Universiti Teknologi MARA, 2017)
Introduction: Body image satisfaction (BIS) may have an effect on body weight, which in turn contributes to healthier lifestyle practices. The present study aimed to measure the BMI of students, and to relate this to the students’ own perceptions of their body image and assessing body image satisfaction using the Stunkard figure rating scale. Methods: A cross sectional study was carried out on 200 students selected by stratified random sampling technique. Variables that were used in the current study are perception of self-body size, ideal body size, and body size satisfaction. The assessment was carried out using the Stunkard figure rating scale. Results: Mean age of the students was 20.4 years. Mean BMI of the boys was 25.63 and of the girls was 25.09. There was a significant difference between perceived body size and body size as per BMI. Overall the girls had significantly more satisfaction with their body image as compared to boys. The body image satisfaction and BMI had positive correlation. Most of the time students thought they were thinner than they actually were, with obvious implications for health and health seeking behaviour. Conclusions: Correct perception of the body size may become the motivation to lose weight and contribute to high success rate in attaining it. A wholesome community approach is needed to change weight status perceptions and improve exercise and dietary behaviour.